1998
DOI: 10.1103/physrevb.57.r11069
|View full text |Cite
|
Sign up to set email alerts
|

Manifestation of history-dependent critical currents via dc and ac magnetization measurements in single crystals ofCeRu2and2Het al.

Abstract: A study of path dependent effects in single crystals of CeRu2 and 2H − N bSe2 show that critical current density Jc of the vortex state depends on its thermomagnetic history over a very large part of (H, T ) parameter space. The path dependence in Jc is absent above the peak position (i.e., H > Hp) of the peak effect region, which we believe identifies the complete loss of order in the vortex structure. The highly disordered FC state can be healed into a relatively ordered vortex lattice by subjecting it to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
35
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 26 publications
5
35
3
Order By: Relevance
“…Using similar measurements close to the peak effect in CeRu 2 and NbSe 2 , [23,36] it was shown that the peak effect arose as a consequence of a first order phase transition [28]. taking cue from these studies, here too we investigate, if the SMP can arise …”
Section: Thermomagnetic History Dependencementioning
confidence: 75%
“…Using similar measurements close to the peak effect in CeRu 2 and NbSe 2 , [23,36] it was shown that the peak effect arose as a consequence of a first order phase transition [28]. taking cue from these studies, here too we investigate, if the SMP can arise …”
Section: Thermomagnetic History Dependencementioning
confidence: 75%
“…The existence of transient states suggests that the disordered phase can be supercooled into the ordered region [21], producing an increasing voltage response, whereas the ordered phase may be superheated into the disordered region, giving a decaying response. In addition to transient effects, pronounced memory effects and hysteretic V(I) curves have been observed near the peak effect in low temperature materials [2,[4][5][6][7][16][17][18][19][20]. Memory effects are also seen in simulations [22].…”
mentioning
confidence: 96%
“…The competition between the flux-line interactions, which order the vortex lattice, and the defects in the sample, which disorder the vortex lattice, produce a remarkable variety of collective behavior [1]. One prominent example is the peak effect in low temperature superconductors, which appears near H c2 when a transition from an ordered to a strongly pinned disordered state occurs in the vortex lattice [2][3][4][5][6][7][8]. In high temperature superconductors, particularly BSCCO samples, a striking "second peak" phenomenon is observed in which a dramatic increase in the critical current occurs for increasing fields.…”
mentioning
confidence: 99%
“…Vortices in type II superconductors, which can be pinned by random defect sites in the material, are a particularly ideal example of such a system since the substrate and lattice interactions can be readily tuned experimentally. In this case, a rich variety of static [1][2][3][4][5][6] and dynamical phases [2,7,8] can occur due to the competition between the repulsive vortex-vortex interactions, which tend to order the vortex lattice, and the attractive vortex-pin interactions, which tend to disorder the vortex lattice. Unlike the early studies of collective pinning of a defect-free elastic lattice, recent experimental and theoretical work point to the importance of topological defects in pinned vortex matter.…”
Section: Introductionmentioning
confidence: 99%